Evaluation of focused multipolar stimulation for cochlear implants in long-term deafened cats. (2nd April 2015) - George, Shefin S; Wise, Andrew K; Fallon, James B; Shepherd, Robert K
Abstract: Objective . Focused multipolar (FMP) stimulation has been shown to produce restricted neural activation using intracochlear stimulation in animals with a normal population of spiral ganglion neurons (SGNs). However, in a clinical setting, the widespread loss of SGNs and peripheral fibres following deafness is expected to influence the effectiveness of FMP. Approach . We compared the efficacy of FMP stimulation to both monopolar (MP) and tripolar (TP) stimulation in long-term deafened cat cochleae ( n = 8). Unlike our previous study, these cochleae contained <10% of the normal SGN population adjacent to the electrode array. We also evaluated the effect of electrode position on stimulation modes by using either modiolar facing or lateral wall facing half-band electrodes. The spread of neural activity across the inferior colliculus, a major nucleus within the central auditory pathway, was used as a measure of spatial selectivity. Main results . In cochleae with significant SGN degeneration, we observed that FMP and TP stimulation resulted in greater spatial selectivity than MP stimulation ( p < 0.001). However, thresholds were significantly higher for FMP and TP stimulation compared to MP stimulation ( p < 0.001). No difference between FMP and TP stimulation was found in any measures. The high threshold levels for FMP stimulation was significantly reduced without compromising spatial selectivity by varying the degree of current focusing (referred as 'partial-FMP' stimulation). Spatial selectivity of all stimulation modes was unaffected by the electrode position. Finally, spatial selectivity in long-term deafened cochleae was significantly less than that of cochleae with normal SGN population (George S S et al 2014 J. Neural Eng. 11 065003 ). Significance . The present results indicate that the greater spatial selectivity of FMP and TP stimulation over MP stimulation is maintained in cochleae with significant neural degeneration and is not adversely affected by electrode position. The greater spatial selectivity of FMP and TP stimulation would be expected to result in improved clinical performance.